2016
DOI: 10.1093/jnen/nlw052
|View full text |Cite
|
Sign up to set email alerts
|

MGMT-Methylated Alleles Are Distributed Heterogeneously Within Glioma Samples Irrespective ofIDHStatus and Chromosome 10q Deletion

Abstract: Several molecular markers drive diagnostic classification, prognostic stratification, and/or prediction of response to therapy in patients with gliomas. Among them, IDH gene mutations are valuable markers for defining subtypes and are strongly associated with epigenetic silencing of the methylguanine DNA methyltransferase (MGMT) gene. However, little is known about the percentage of MGMT-methylated alleles in IDH-mutated cells or the potential association between MGMT methylation and deletion of chromosome 10q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Until last year, diffuse gliomas were classified on the basis of histological criteria and 2007 World Health Organization (WHO) grading [ 2 ]. The increasing and extensive characterization of the genomic landscape of gliomas prompted the identification of genetic and epigenetic markers useful for tumor molecular classification; in the future, these molecular signatures could also represent actionable targets in gliomas, as is already the case for other cancers [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until last year, diffuse gliomas were classified on the basis of histological criteria and 2007 World Health Organization (WHO) grading [ 2 ]. The increasing and extensive characterization of the genomic landscape of gliomas prompted the identification of genetic and epigenetic markers useful for tumor molecular classification; in the future, these molecular signatures could also represent actionable targets in gliomas, as is already the case for other cancers [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, another study found no influence of 10q LOH over OS independently of MGMT methylation status, but it was performed on a cohort of mix GBM and low grade gliomas. 40 We observed no PFS differences (P = .79) between group 1 and group 2, probably due to the fact that the majority of patients had tumor progression within the first 8 months of follow-up. This lack of association can also be explained by the inherent difficulties of determination of true tumor progression, distinguished from pseudoprogression and radionecrosis.…”
Section: Univariate Analysismentioning
confidence: 56%
“…However, current comprehensive treatments, comprising surgery, radiotherapy, and chemotherapy, have not achieved the desired therapeutic effects [2,3]. With the continuous development of genomics, researchers are paying closer attention to the molecular expression changes of glioma patients, such as IDH status, MGMT promoter methylation, and 1p/19q codeletion [6,7]. Therefore, we explored biomarkers that could guide the early diagnosis, treatment, and prognosis of gliomas through genomic data.…”
Section: Introductionmentioning
confidence: 99%